Sistem Informasi Pendaftaran Pasien Berbasis WEB di Puskesmas Taratara Kota Tomohon. - Riylokheni Hotman Loho; Jantje D. Prang; Mahardika I. Takaendengan (Faculty of Mathematics and Natural Sciences Sam Ratulangi University, 2023)
The patient registration process in the current era of technological development is increasingly sophisticated and makes it easier for the public to apply it. Taratara Health Center in its application of patient registration is still done manually. For this reason, with existing technological developments, patient registration can be carried out online through a website-based patient registration system. The purpose of making this website-based patient registration is to make it easier for patients to register, so they don't have to wait at the puskesmas for a long time. The system was built and developed using the waterfall development method which was carried out in stages starting from analysis, design, coding, testing and implementation. The results of this online patient registration information system study have an effect on patient waiting time at the Taratara Health Center.